Identification of the major HHV‐6 antigen recognized by cerebrospinal fluid IgG in multiple sclerosis. (12th April 2014) - Alenda, R.; Álvarez‐Lafuente, R.; Costa‐Frossard, L.; Arroyo, R.; Mirete, S.; Álvarez‐Cermeño, J. C.; Villar, L. M.
<x xml:space="preserve">Abstract</x> Background and purpose Different data show an association between human herpesvirus 6 (HHV‐6) and multiple sclerosis (MS). Intrathecal anti‐HHV‐6 immunoglobulin G (IgG) was detected in MS patients, but the antigen recognized by cerebrospinal fluid (CSF) IgG has not been characterized yet. Our objective was to identify the HHV‐6 antigens recognized by IgG present in the CSF of patients with MS. Methods Cerebrospinal fluid IgG of 15 MS patients and eight patients with other neurological diseases was purified on protein G Sepharose columns. Purified IgG from every patient was linked to a CNBr‐activated Sepharose 4B column. Fifty micrograms of viral extract was applied to each column. Bound proteins were eluted and analysed by SDS‐PAGE and silver staining. The viral protein was characterized by mass spectrometry. Results A protein of 150 kD was eluted from CSF IgG columns of three of eight patients with primary progressive MS and one of seven with relapsing−remitting MS. After digestion and mass spectrometry analysis 10 peptides were found with 100% homology with the major capsid protein of the HHV‐6A. Discussion These findings confirm the presence of anti‐HHV‐6 IgG in CSF of MS patients, particularly in progressive forms, and identify major capsid protein as the major antigen recognized by CSF IgG from MS patients.